Protopleurobema: a new genus of freshwater bivalve from the Lower Cretaceous of the Cameros basin (NW Spain) - Delvene, Graciela; Rafael Araujo, Rafael (Journal of Iberian Geology, 2009)
A new genus of fossil bivalve from the Lower Cretaceous of the Cameros Basin is described and designated Protopleurobema. As well as the type material of Unio numantinus (Palacios and Sánchez, 1885), we examined 805 specimens discovered in deposits comprising unit D of the lithological Urbión Group of Upper Barremian-Lower Aptian age. This new taxon is compared here to all the available closely related Mesozoic genera described in the literature. A large number of juvenile and adult specimens of Protopleurobema numantina (Palacios and Sánchez, 1885) were found in what was interpreted as a palaeoecological association. The presence of bivalves (Unionoida) and gastropods of the genus Viviparus indicate the freshwater nature of the environment.